2015
DOI: 10.1007/s00223-015-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Ablation and Vitamin D Deficiency Result in Reduced Grip Strength, Altered Muscle Fibers, and Increased Myostatin in Mice

Abstract: Vitamin D deficiency is associated with muscle weakness, pain, and atrophy. Serum vitamin D predicts muscle strength and age-related muscle changes. However, precise mechanisms by which vitamin D affects skeletal muscle are unclear. To address this question, this study characterizes the muscle phenotype and gene expression of mice with deletion of vitamin D receptor (VDRKO) or diet-induced vitamin D deficiency. VDRKO and vitamin D-deficient mice had significantly weaker grip strength than their controls. Weakn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
124
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 38 publications
9
124
0
Order By: Relevance
“…Secondly, our dietary intervention was fairly short-term (6 wk) compared with prior studies (where deficiency was established for Ն2 mo). Time-related effects of deficiency on peripheral muscle performance are supported by studies in which mice that received a vitamin D-depleted diet for 3 mo showed a greater deficit in grip strength than mice that received a vitamin D-depleted diet for only 2 mo (13). Lastly, we studied the EDL instead of the soleus or epitrochlearis that were studied by others (27,32).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Secondly, our dietary intervention was fairly short-term (6 wk) compared with prior studies (where deficiency was established for Ն2 mo). Time-related effects of deficiency on peripheral muscle performance are supported by studies in which mice that received a vitamin D-depleted diet for 3 mo showed a greater deficit in grip strength than mice that received a vitamin D-depleted diet for only 2 mo (13). Lastly, we studied the EDL instead of the soleus or epitrochlearis that were studied by others (27,32).…”
Section: Discussionmentioning
confidence: 94%
“…Doucet et al demonstrated phosphorylation of Akt/ FOXO in nonhypoxemic COPD patients with muscle wasting compared with COPD patients with preserved muscle mass (8a). Recent studies from Girgis et al (13) showed that skeletal muscle from vitamin D receptor knockout or vitamin D-deficient mice exhibits simultaneous upregulation of myostatin (growth inhibition) and myogenic markers MyoD and Myf 5 vs. control mice. Similarly, models of insulin resistance also exhibit aberrant or hyperactive mTOR signaling under fasted conditions, as does aging muscle (10,37).…”
Section: Diaphragmmentioning
confidence: 97%
“…Although not yet tested in DMD, emerging evidence shows that vitamin D deficiency/supplementation influences the expression/secretion of certain myokines. VDR ablation and vitamin D deficiency increased MSTN expression; vitamin D supplementation inhibited its expression in C2C12 skeletal muscle cells, and VDR activator usage is related to lower serum MSTN levels in patients undergoing peritoneal dialysis . A recent study showed that vitamin D supplementation inhibited IL‐6 surge in tail‐suspended mice (disuse‐induced muscle atrophy model); and serum vitamin D concentration was significantly and negatively correlated with the serum IL‐6 in infertile women with tubal factor infertility .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D may regulate insulin sensitivity in skeletal muscle (25), possibly by upregulating insulin receptors expression (26), and enhancing the insulin signaling pathway (27). Vitamin D may alter the serum levels of muscle growth factors and atrophy markers as reported in an animal study (28). Furthermore, it has been suggested that vitamin D may directly contribute to myoblast proliferation and differentiation in animal (29), and human cells (30) by regulating gene transcription via vitamin D receptor (VDR) signaling pathway.…”
Section: Discussionmentioning
confidence: 86%